SEMIGROUP ACTION FOR HUTCHITSON OPERATOR OF ITERATED FUNCTION SYSTEM (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this article, we are trying to see the Iterated function system or more generally a skew product as formation a semigroup action system. We will try to implement more semigroup action properties on itself. For this purpose, we introduce a semigroup action corresponding Iterated function system and explain more properties of itself then with considering Hutchitson operator on Iterated function system, we try consider the corresponding semigroup action for Iterated function system and achive more its properties.